Answer:
B. (x+1)^2 + (y-7)^2=196
Step-by-step explanation:
The equation is (x-h)^2 + (y-k)^2=r^2
h=-1,k=7 and r=14
(x-(-1))^2 + (y-7)^2= 14^2
(x+1)^2 + (y-7)^2 = 196
Answer:
46.9
Step-by-step explanation:
i looked it up
According to the question,
6x + 90 = -42
<h3>To Find:</h3>
The value of x.
<h3>Solution:</h3>
6x = -42 + 90
or, x = 48/6
or, x = 8
<h2>Answer:</h2>
The value of x is 8.
Answer:
OWO
Step-by-step explanation:
ADD Divide
Answer:
2a
Step-by-step explanation:
We can combine like terms.
There are 2 'a' s in the expression, so we can rewrite a + a as 2a.